The impact of cannabinoid receptor 1 absence on mouse liver mitochondria homeostasis: insight into mitochondrial unfolded protein response - Senese, Rosalba; Petito, Giuseppe; Silvestri, Elena; Ventriglia, Maria; Mosca, Nicola; Potenza, Nicoletta; Russo, Aniello; Falvo, Sara; Manfrevola, Francesco; Cobellis, Gilda; Chioccarelli, Teresa; Porreca, Veronica; et al. (Frontiers in Cell and Developmental Biology, 2024)
The contribution of Cannabinoid type 1 receptor (CB1) in mitochondrial energy transduction mechanisms and mitochondrial activities awaits deeper investigations. Our study aims to assess the impact of CB1 absence on the mitochondrial compartment in the liver, focusing on both functional aspects and remodeling processes. We used CB1 -/-and CB1 +/+ male mice. Cytochrome C Oxidase activity was determined polarographically. The expression and the activities of separated mitochondrial complexes and supercomplexes were performed by using Blue-Native Page, Western blotting and histochemical staining for in-gel activity. Key players of Mitochondrial Quality Control processes were measured using RT-qPCR and Western blotting. Liver fine sub-cellular ultrastructural features were analyzed by TEM analysis. In the absence of CB1, several changes in the liver occur, including increased oxidative capacity, reduced complex I activity, enhanced complex IV activity, general upregulation of respiratory supercomplexes, as well as higher levels of oxidative stress. The mitochondria and cellular metabolism may be affected by these changes, increasing the risk of ROSrelated damage. CB1 -/-mice show upregulation of mitochondrial fusion, fission and biogenesis processes which suggests a dynamic response to the absence of CB1. Furthermore, oxidative stress disturbs mitochondrial proteostasis, initiating the mitochondrial unfolded protein response (UPR mt ).We noted heightened levels of pivotal enzymes responsible for maintaining mitochondrial integrity, along with heightened expression of molecular chaperones and transcription factors associated with cellular stress reactions. Additionally, our discoveries demonstrate a synchronized reaction to cellular stress, involving both UPR mt and UPR ER pathways.